Micro-credentials and Modern Learners: Insights into Student Perceptions and Acceptance - Eric S. Parilla; Yolanda S. Lao; Charliemaine Bullalayao; Shiela S. Navasca1 Navasca (Research Synergy Foundation, 2024)
Flexible, skill-based routes have been the emphasis of education in the post-pandemic era. Following the outbreak of COVID-19, there has been a rise in the popularity of nontraditional education methods that emphasize skills rather than knowledge. This has led to an increase in demand for online classes that are meant to develop relevant job skills among individuals. This research investigates students’ opinions and attitudes toward micro-credentials. However, while student reactions are generally positive and sometimes even modest, they confirm micro-credentials of their uniqueness, flexibility in application, as well as practicality regarding immediate professional needs One striking finding is that while 63.36% were graduates of college, only 51.73% knew where to find micro-credential courses that match their field of study. The data from 2,115 valid respondents showed an average composite mean score of 2.96 for perception and 3.02 for acceptance, suggesting that participants were cautious about the potential of micro-credentials. Nevertheless, there is still a disconnect between the way they are used now vis-à-vis how institutions or professional bodies view them, as well as whether or not these courses are likely to have any enduring value or consideration in the labor market. Therefore, the present results indicate that academic institutions must collaborate with businesses to meet their labor market’s needs with shorter programs, which should also be acceptable in the sphere of education. The aim of this article is to advance the field of micro-credentials research while providing a foundation for future studies on their significance in education and career development.